The Role Of Consumer Trust As An Intervening Variable In Purchasing Decisions In Lazada E-Commerce: A Study Of Indonesian Society - Firdaus Firdaus; Martini Martini; Sri Sulistiyaningsih ; Meizar Effendi (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research aims to identify the direct impact of online customer reviews and online customer ratings on trust and purchasing decisions, as well as the indirect impact of online customer reviews and online customer ratings through trust on purchasing decisions on Lazada e-commerce for Indonesian society. The research method used is quantitative with the help of a questionnaire as the main instrument. The sample collected was 250 respondents selected through purposive sampling and the data was processed with the help of SEM AMOS. The results of structural equation modeling (SEM) analysis show that online customer reviews and customer ratings have a positive and significant impact on trust and purchasing decisions directly, the same thing applies to indirect relationships, showing that the role of trust as an intervening variable can strengthen student decisions. to shop on Lazada e-commerce. This can happen because Lazada always tries to provide transparent services to consumers, and this has an impact on consumer trust in shopping at Lazada.